(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
While the environment has been a perennial theme in human thought, the environment and how humans value, use and think about it has become an increasingly central and important aspect of recent social theory. It has become clear that the present generation is faced with a series of unique environmental dilemmas, largely unprecedented in human history.Environment and Social Theory outlines the complex interlinking of the environment, nature and social theory from ancient and pre-modern thinking to contemporary social theorising. It explores the essentially contested character of the environment and nature within social theory, and draws attention to the need for critical analysis whenever the term ‘nature’ and ‘environment’ are used in debate and argument.